Stimulation of Aryl Hydrocarbon Hydroxylase Induction in Cell Cultures by Interferon - Nebert, Daniel W. (1973)
In cell cultures previously treated with homologous interferon, the magnitude of antiviral activity and the degree of stimulation of aryl hydrocarbon hydroxylase induction appear to be directly related. In a highly purified mouse interferon preparation, the factor stimulating hydroxylase induction and the factor directing antiviral activity are inactivated by heating to 70 C or by treating with trypsin. Also, both activities demonstrate species specificity.